Comparative efficacy of acupuncture-related therapy for migraine: A systematic review and network meta-analysis - Song, Yanjuan; Li, Tong; Ma, Chunlian; Liu, Hui; Liang, Fengxia; Yang, Yi (Frontiers in Neurology, 2022)
Background Migraine is a worldwide disabling chronic brain disorder, some studies suggest acupuncture-related therapy plays an important role in raising efficiency rates and reducing migraine attacks. However, clinical trials comparing the efficacy of different interventions for migraine are limited and controversial. This network meta-analysis (NMA) was performed to review all randomized controlled trials (RCTs) comparing the effects of acupuncture-related therapy for migraine. Methods Randomized controlled trials (RCTs) of acupuncture-related therapy for migraine were searched in the following databases from the date of database inception to March 31, 2022, including PubMed, Embase, Cochrane Library, Web of Science, China National Knowledge Infrastructure (CNKI), VIP Database, Wanfang Database, and Chinese Biomedical Database (CBM). The primary endpoint was visual analog scale (VAS) scores. The secondary endpoints were the number of migraine days, duration of migraine, and frequency of migraine attacks. We used Cochrane risk of bias to assess the quality of evidence for outcomes. Results Thirty-nine studies involving 4379 patients with 13 different acupuncture-related methods were evaluated. According to surface under the cumulative ranking curve value, acupoint injection was ranked the highest (98.0%) in VAS scores, followed by acupoint implantation (79.0%); electroacupuncture was the optimal intervention method (82.4%) in the number of migraine days, followed by embedding needle therapy (73.1%); embedding needle therapy ranked first (99.9%) in the duration of migraine, followed by acupoint injection (77.4%); acupoint injection was the best intervention (99.3%) in the frequency of migraine attacks, followed by conventional acupuncture plus massage (73.8%). Conclusion These results provide preliminary evidence that acupuncture-related therapy could be recommended as one of the effective treatments for migraine. Conventional acupuncture has significant effects on improving VAS scores, the number of migraine days, duration of migraine, and frequency of migraine attacks. However, more high-quality studies should be carried out to verify this finding. Systematic review registration https://inplasy.com/, identifier: INPLASY202110035.